Life at the intersection: The lateral relations of han mannen, mannen, and den mannen - Bloom, Barthe (Constructional Approaches to Nordic Languages, 2023)
In colloquial Norwegian, han ‘he’ and hun ‘she’ can occur as a determiner with common nouns with human reference (e.g., han mannen, lit. ‘he man-the’). This study investigates the lateral relations of this construction (henceforth: han mannen) and two other definite-referring constructions with human reference: noun phrases that contain the adnominal determiner den (i.e., den mannen) and those that realize definiteness by a suffixed article (i.e., mannen). The study argues that han mannen lives at the intersection of these two constructions, i.e., that it is motivated by two constructions to which it is laterally related. The lateral relations between the constructions are evaluated by random forests, variable importance measures, and partial dependence plot
Keywords: lateral relations; Norwegian; han mannen; definite determiners